“If God is dead, not everything is aloud”. An aesthetic Interpretation of Kant¨s Postulates. - Parra, Lisímaco (Con-Textos Kantianos. International Journal of Philosophy, 2024)
Starting from the difference between foundation and effectiveness, established by H. Kelsen, I interpret the difference between the questions “what should I do?” and, “If I do what I should, what can I expect?” The postulates of the existence of God and the immortality of the soul are interpreted as aesthetic strategies belonging to the second question. A redefinition of the concept of happiness would imply the need to build new strategies, all of them clearly differentiable from the moral mandate.